Biomechanical evaluation of a novel individualized zero-profile cage for anterior cervical discectomy and fusion: a finite element analysis - Wang, Yang; Liu, Yang; Zhang, Aobo; Han, Qing; Jiao, Jianhang; Chen, Hao; Gong, Xuqiang; Luo, Wangwang; Yue, Jing; Zhao, Xue; Wang, Jincheng; Wu, Minfei (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Anterior cervical discectomy and fusion (ACDF) is a standard procedure for treating symptomatic cervical degenerative disease. The cage and plate constructs (CPCs) are widely employed in ACDF to maintain spinal stability and to provide immediate support.However, several instrument-related complications such as dysphagia, cage subsidence, and adjacent segment degeneration have been reported in the previous literature. This study aimed to design a novel individualized zero-profile (NIZP) cage and evaluate its potential to enhance the biomechanical performance between the instrument and the cervical spine.The intact finite element models of C3-C7 were constructed and validated. A NIZP cage was designed based on anatomical parameters of the subject's C5/6. The ACDF procedure was simulated and the CPCs and NIZP cage were implanted separately. The range of motion (ROM), intradiscal pressure (IDP), and peak von Mises stress of annulus fibrosus were compared between the two surgical models after ACDF under four motion conditions.Additionally, the biomechanical performance of the CPCs and NIZP cage were evaluated.Compared with the intact model, the ROM of the surgical segment was significantly decreased for both surgical models under four motion conditions. Additionally, there was an increase in IDP and peak von Mises stress of annulus fibrosus in the adjacent segment. The NIZP cage had a more subtle impact on postoperative IDP and peak von Mises stress of annulus fibrosus in adjacent segments compared to CPCs. Meanwhile, the peak von Mises stresses of the NIZP cage were reduced by 90.0-120.0 MPa, and the average von Mises stresses were reduced by 12.61-17.56 MPa under different motion conditions. Regarding the fixation screws, the peak von Mises stresses in the screws of the NIZP cage increased by 10.0-40.0 MPa and the average von Mises stresses increased by 2.37-10.10 MPa.The NIZP cage could effectively reconstruct spinal stability in ACDF procedure by finite element study. Compared with the CPCs, the NIZP cage had better biomechanical performance, with a lower stress distribution on the cage and a more moderate effect on the adjacent segmental discs. Therefore, the NIZP cage could prevent postoperative dysphagia as well as decrease the risk of subsidence and adjacent disc degeneration following ACDF.